THE EFFECT OF PROBLEM-BASED LEARNING MODEL ON THE SOCIOLINGUISTICS LEARNING OUTCOMES OF PRIVATE UNIVERSITY STUDENTS IN ACEH - Budi Rizka; Lismalinda (English Education Department, 2021)
This study aims to analyze the effect of the application of the problem based learning model in sociolinguistic learning on student learning outcomes of English Education at private universities in Aceh. This study used an experimental method with a research form that is pre-experimental design and one-group pretest-postest design experimental design. The population in this study were 40 students from private universities in Aceh. The sample in this study was the entire population of 40 students who were divided into two experimental groups, where Experiment Group A 20 people and Experiment Group B 20 people. The research instrument used was the learning outcome in the form of a multiple choice test of 20 questions. The data collection technique in this study is a measurement technique. Hypothesis test results using t-stat which is obtained in Experiment group A tstat (-18.6) < t Critical two-tail (2.093) with an average value of pre-test 59.75 and posttest 78 and Experiment group B tstat (-27 , 5) < t Critical two-tail (2,093) with an average score of 58 pre-test and 78 post-test. From the results of these calculations it can be concluded that there is an effect of using problem based learning models on learning outcomes in sociolinguistic learning of private university students in Aceh.